On the predictability of volcano-tectonic events by low frequency seismic noise analysis at Teide-Pico Viejo volcanic complex, Canary Islands - M. Tárraga (Natural Hazards and Earth System Sciences, 2006)
The island of Tenerife (Canary Islands, Spain), is showing possible signs of reawakening after its last basaltic strombolian eruption, dated 1909 at Chinyero. The main concern relates to the central active volcanic complex Teide - Pico Viejo, which poses serious hazards to the properties and population of the island of Tenerife (Canary Islands, Spain), and which has erupted several times during the last 5000 years, including a subplinian phonolitic eruption (Montaña Blanca) about 2000 years ago. In this paper we show the presence of low frequency seismic noise which possibly includes tremor of volcanic origin and we investigate the feasibility of using it to forecast, via the material failure forecast method, the time of occurrence of discrete events that could be called Volcano-Tectonic or simply Tectonic (i.e. non volcanic) on the basis of their relationship to volcanic activity. In order to avoid subjectivity in the forecast procedure, an automatic program has been developed to generate forecasts, validated by Bayes theorem. A parameter called 'forecast gain' measures (and for the first time quantitatively) what is gained in probabilistic terms by applying the (automatic) failure forecast method. The clear correlation between the obtained forecasts and the occurrence of (Volcano-)Tectonic seismic events - a clear indication of a relationship between the continuous seismic noise and the discrete seismic events - is the explanation for the high value of this 'forecast gain' in both 2004 and 2005 and an indication that the events are Volcano-Tectonic rather than purely Tectonic.